Menstruation and Fasting in Islamic Discourse: A Study of Muhammadiyah Youth and KUPI Interpretations - Yulianti Muthmainnah (Millati: Journal of Islamic Studies and Humanities)
This research discusses the views of KUPI Ulama regarding menstruation. In 2020, the issue of menstruating women fasting went viral on social media, and the KUPI network faced pressure. The purpose of the study was to examine the opinions of KUPI scholars and female activists of the organization about fasting for women who menstruate. This study used a qualitative method, combining literature review, interviews and open questions during 'Gender Equality' training and 'Reproductive Health' discussion via zoom (available on youtube). The theory used is grounded theory. namely the experiences of women and men in the KUPI Network who have the idea that menstruating women can fast as primary data. The research respondents were young women aged between 20 to 42 years who are active in Muhammadiyah and women's movements. The first result showed that women in the KUPI Network who agreed that menstruating women could fast were attacked for their opinion and undermined for their expertise, and were seen as being more associated with their body than men in the KUPI Network. Second, young women who are active in Muhammadiyah but are not involved in the women's movement argue that the prohibition of fasting and sexual relations during menstruation is because it is considered "dirty". Third, respondents who are active in Muhammadiyah and the women's movement believe that menstruation during fasting is permissible, depending on the woman's ability, and that menstruation is not something dirty. Fourth, women who are active in the women's movement and KUPI but not involved in Muhammadiyah say that women can fast during menstruation because it is a normal reproductive cycle for women.